Pengaruh Sinetron Ikatan Cinta Di RCTI Terhadap Minat Menonton Ibu-Ibu Rumah Tangga di Kota Ambon - Amelia Tahitu; Jimmy Purwata Mangasi Sirait (Fakultas Ilmu Sosial dan Ilmu Politik, 2022)
This research with the title of the influence of love bond soap operas on the interest of watching housewives in Amantelu Village, Ambon City. The problem of this research is to want to know how the influence of Sintron Ikatan Cinta RCTI as a television drama on the interest in watching housewives or audiences in Amantelu Village, Ambon City. This research aims to find out and analyze the influence of Sinetron Ikatan Cinta in RCTI on the interest in watching housewives in Amantelu Village, Ambon City, as a mass media whose function is to provide information, knowledge and entertainment. This research is important to do considering that the issue of interest in watching soap operas on television is part of the needs of individuals as social creatures who need information about entertainment for themselves and others.To find out the problem of research on the influence of love soap operas in RCTI on the interest in watching housewives in Amantelu Village, Ambon City, and adjusted to the purpose and benefits of research, this study uses quantitative methods. The results of the study with statistical tests can be explained that the Love Bond Soap Opera with measuring indicators, namely; Storyline, main actor, message obtained, soap opera appeal, very significant influence on the interest of watching in housewives in Ambon City. It is based on the results of the t Test which means the hypothesis is accepted. Based on the Value Determination test (r^2) showed that 50.1% of the influence of interest in watching housewives (Y) was influenced by the soap opera love bond (X). The remaining 49.9% was influenced by other factors not studied in the study.Variable Y is the interest in watching housewives in Amantelu Village – Ambon City with indicators of feelings of pleasure / likes, attractions / encouragement, attention, and involvement in an object has a significant effect on variable X so that the hypothesis results are accepted.